IDNLearn.com connects you with a community of knowledgeable individuals ready to help. Receive prompt and accurate responses to your questions from our community of knowledgeable professionals ready to assist you at any time.

2. Simplify and solve each of the following equations containing symbols of inclusion.

a. [tex]2(3x + 1) = 8[/tex]

b. [tex]4 + 18d = [(2 + 2) + 3(2d - 2)][/tex]

c. [tex]4(u + 3) = 5u - 3u[/tex]

d. [tex]v + 8 = [(3v + 4 - v) - 2] + 4[/tex]

e. [tex]\{[(3 + 4) - 6x \cdot 2] + 10\} = 5[/tex]

f. [tex]\{[(7 \cdot 2x) - (7 \cdot 7) + 4x] + 85\} = 0[/tex]


Sagot :

Let's solve each equation step-by-step.

### Part (a): [tex]\(2(3x + 1) = 8\)[/tex]

1. Distribute the 2 on the left-hand side:
[tex]\[2 \cdot (3x) + 2 \cdot 1 = 8\][/tex]
[tex]\[6x + 2 = 8\][/tex]

2. Subtract 2 from both sides to isolate the term with [tex]\(x\)[/tex]:
[tex]\[6x = 8 - 2\][/tex]
[tex]\[6x = 6\][/tex]

3. Divide both sides by 6:
[tex]\[x = \frac{6}{6}\][/tex]
[tex]\[x = 1\][/tex]

So the solution is [tex]\(x = 1\)[/tex].

### Part (b): [tex]\(4 + 18d = [(2 + 2) + 3(2d - 2)]\)[/tex]

1. Simplify inside the brackets on the right-hand side:
[tex]\[(2 + 2) + 3(2d - 2)\][/tex]
[tex]\[4 + 3(2d - 2)\][/tex]

2. Distribute the 3:
[tex]\[4 + 3 \cdot 2d - 3 \cdot 2\][/tex]
[tex]\[4 + 6d - 6\][/tex]

3. Simplify:
[tex]\[4 + 18d = 4 + 6d - 6\][/tex]
[tex]\[4 + 18d = 6d - 2\][/tex]

4. Subtract 6d from both sides:
[tex]\[4 + 12d = -2\][/tex]

5. Subtract 4 from both sides:
[tex]\[12d = -2 - 4\][/tex]
[tex]\[12d = -6\][/tex]

6. Divide by 12:
[tex]\[d = \frac{-6}{12}\][/tex]
[tex]\[d = -\frac{1}{2}\][/tex]

So the solution is [tex]\(d = -\frac{1}{2}\)[/tex].

### Part (c): [tex]\(4(u + 3) = 5u - 3u\)[/tex]

1. Distribute the 4 on the left-hand side:
[tex]\[4u + 12 = 2u\][/tex]

2. Subtract 2u from both sides:
[tex]\[4u - 2u + 12 = 0\][/tex]
[tex]\[2u + 12 = 0\][/tex]

3. Subtract 12 from both sides:
[tex]\[2u = -12\][/tex]

4. Divide by 2:
[tex]\[u = \frac{-12}{2}\][/tex]
[tex]\[u = -6\][/tex]

So the solution is [tex]\(u = -6\)[/tex].

### Part (d): [tex]\(v + 8 = [(3v + 4 - v) - 2] + 4\)[/tex]

1. Simplify inside the brackets on the right-hand side:
[tex]\[ (3v + 4 - v) - 2 + 4\][/tex]
[tex]\[ (2v + 4) - 2 + 4\][/tex]
[tex]\[ 2v + 8 - 2\][/tex]
[tex]\[ 2v + 6\][/tex]

2. Now, the equation is:
[tex]\[v + 8 = 2v + 6\][/tex]

3. Subtract [tex]\(v\)[/tex] from both sides:
[tex]\[8 = v + 6\][/tex]

4. Subtract 6 from both sides:
[tex]\[v = 2\][/tex]

So the solution is [tex]\(v = 2\)[/tex].

### Part (e): [tex]\(\{[(3 + 4) - 6x \cdot 2] + 10\} = 5\)[/tex]

1. Simplify inside the brackets:
[tex]\[(3 + 4) - 6x \cdot 2\][/tex]
[tex]\[7 - 12x\][/tex]

2. Add the 10:
[tex]\[ (7 - 12x) + 10 = 5\][/tex]
[tex]\[ 17 - 12x = 5\][/tex]

3. Subtract 17 from both sides:
[tex]\[-12x = 5 - 17\][/tex]
[tex]\[-12x = -12\][/tex]

4. Divide by -12:
[tex]\[x = \frac{-12}{-12}\][/tex]
[tex]\[x = 1\][/tex]

So the solution is [tex]\(x = 1\)[/tex].

### Part (f): [tex]\(\{[(7 \cdot 2x) - (7 \cdot 7) + 4x] + 85\} = 0\)[/tex]

1. Simplify inside the brackets:
[tex]\[(7 \cdot 2x) - (7 \cdot 7) + 4x\][/tex]
[tex]\[14x - 49 + 4x\][/tex]
[tex]\[18x - 49\][/tex]

2. Add the 85:
[tex]\[ (18x - 49) + 85 = 0\][/tex]
[tex]\[ 18x + 36 = 0\][/tex]

3. Subtract 36 from both sides:
[tex]\[18x = -36\][/tex]

4. Divide by 18:
[tex]\[x = \frac{-36}{18}\][/tex]
[tex]\[x = -2\][/tex]

So the solution is [tex]\(x = -2\)[/tex].

In summary, the solutions are:
a) [tex]\(x = 1\)[/tex]
b) [tex]\(d = -\frac{1}{2}\)[/tex]
c) [tex]\(u = -6\)[/tex]
d) [tex]\(v = 2\)[/tex]
e) [tex]\(x = 1\)[/tex]
f) [tex]\(x = -2\)[/tex]